A MORPHOLOGICAL STUDY OF SOME SPECIES OF THE GENUS Medicago L. (Fabaceae) IN KURDISTAN /IRAQ - Abdulrazaq, Kazheen Jomaa; Abdulrahman, Shamiran; Muhammed, Jotyar Jassim (Science Journal of University of Zakho, 2026)
This study provides a thorough morphological analysis of Medicago L. species in Iraq’s Kurdistan Region, with the aim of discriminating taxa using a range of vegetative and reproductive traits. Variations in petiole size, leaflet morphology, floral attributes, and pod characteristics were highlighted in morphological examinations of the collected specimens. All the characteristics that were looked at showed distinct interspecific differences. Medicago polymorpha’s petiole length ranged from 3.8–5.3 mm, while M. rigidula’s ranged from 19–39 mm. with length-to-width ratios of 1.22 for M. radiata and 1.80 for M. noeana, there were notable variation in leaflet proportions, indicating significant shape variation. Peduncle length, in example, differed significantly between M. radiata and M. noeana, measuring 3–8 mm and 10–30 mm, respectively. As pod sizes ranged from 2.5–5.5 mm in M. minima to 13–18 mm in M. radiata, pod shape proved highly diagnostic. Additionally, species identification was made easier by variations in coil number (5–7 coils in M. minima). The identification of M. rigidula subsp. sinskiae as a new distributional record for the Kurdistan Region of Iraq is a significant result of our research. Note that the taxon formerly known as M. sinskiae now has a recognized scientific designation, M. rigidula subsp. sinskiae. All things considered, the observed morphological variety highlights the genus Medicago’s ecological difference and offers crucial baseline information for further taxonomic, ecological, and conservation research.